Improving Ips Learning Outcomes About Currency And Its Use Through Experimental Methods On Class III Students Of State 001 Elementary School 001 Kepenuhan Academic Year 2019/2020 - Sri Riawati (Indonesian Journal of Basic Education, 2022)
This study aims to improve the learning outcomes of third grade elementary school students at State 001 Kepenuhan on the subject matter of Currency and Its Uses through the experimental method. This can be seen from the results of the final test of learning social studies subjects on currency material and its uses, from the number of third grade students as many as 23 students with a KKM of 70, only 10 students were able to reach the KKM while the 13 students had not reached the KKM, while only reaching the KKM. Class average. After reflecting on the results of the implementation of learning improvements, it turns out that the experimental method has advantages, namely that students are more enthusiastic in learning because students do themselves mention the names of currencies and their uses are known by themselves, and student learning outcomes are more improved than before.